Repo-Man coordinates chromosomal reorganization with nuclear envelope reassembly during mitotic exit. - Vagnarelli, P; Ribeiro, S; Sennels, L; Sanchez-Pulido, L; de Lima Alves, F; Verheyen, T; Kelly, D; Ponting, C; Rappsilber, J; Earnshaw, W (2011)
Repo-Man targets protein phosphatase 1 γ (PP1γ) to chromatin at anaphase onset and regulates chromosome structure during mitotic exit. Here, we show that a Repo-Man:PP1 complex forms in anaphase following dephosphorylation of Repo-Man. Upon activation, the complex localizes to chromosomes and causes the dephosphorylation of histone H3 (Thr3, Ser10, and Ser28). In anaphase, Repo-Man has both catalytic and structural functions that are mediated by two separate domains. A C-terminal domain localizes Repo-Man to bulk chromatin in early anaphase. There, it targets PP1 for the dephosphorylation of histone H3 and possibly other chromosomal substrates. An N-terminal domain localizes Repo-Man to the chromosome periphery later in anaphase. There, it is responsible for the recruitment of nuclear components such as Importin β and Nup153 in a PP1-independent manner. These observations identify Repo-Man as a key factor that coordinates chromatin remodeling and early events of nuclear envelope reformation during mitotic exit.